AJHP: Redesigned - Jill A. Sellers (American Journal of Health-System Pharmacy, 2000)
Purpose To evaluate pharmacy technicians' perceptions of pharmacist leadership styles and their impact on retention, career commitment, organizational commitment, resilience, and engagement in expanded or advanced responsibilities within one division of a large community pharmacy chain. Methods A cross-sectional survey was conducted among pharmacy technicians in 22 community pharmacies in eastern Tennessee. The self-administered online survey incorporated validated components from the Multifactor Leadership Questionnaire (MLQ) and Brief Resilience Scale, as well as coworker support measures. Technicians were recruited using a modified Dillman's approach, with both certified and noncertified individuals invited to participate. Descriptive and inferential statistics, including chi-square tests, t tests, analysis of variance, and correlational analyses, were used to assess relationships between leadership styles and technician outcomes. Pharmacies were stratified into tertiles based on MLQ scores to examine organizational-level differences. Transformational leadership emphasizes coaching and inspiration, whereas transactional leadership emphasizes structured expectations and performance-based rewards. Results Among 175 invited technicians, the response rate was 48.6%, representing 86.4% of surveyed pharmacies. Top-tertile pharmacies had significantly higher mean scores for both transformational and transactional leadership (P < 0.05) as well as leadership outcomes. Transformational leadership was strongly correlated with coworker support (r = 0.688, P < 0.001) and weakly correlated with resilience (r = 0.218, P < 0.05). Transactional leadership was moderately correlated with coworker support (r = 0.487, P < 0.001) and organizational commitment (r = 0.402, P < 0.001) and weakly correlated with resilience (r = 0.287, P < 0.05). Stratification revealed clear differences in technician retention, commitment, and resilience across leadership engagement levels. Conclusion Higher levels of transformational and transactional leadership, as measured by the MLQ, were associated with more favorable technician outcomes, including stronger coworker support, higher organizational commitment, and greater resilience. Stratifying pharmacies by leadership engagement highlights the organizational impact of effective leadership behaviors. Fostering transformational leadership supported by constructive transactional structure among pharmacists may enhance technician outcomes and support resilient, high-performing pharmacy teams.